Hypoglycemic and Hypotriglyceridemic Effects of Aloe Vera Whole Leaf and Sitagliptin in Diabetic Rats - Javaid, Sobia (International Journal of Pathology, 2020)
Background:. Aloe Vera with excellent metabolic properties is playing wonders in diabetes treatment. Objective: “To compare the hypoglycemic and hypotriglyeridemic effects of Aloe Vera whole leaf and Sitagliptin on Streptozotocin induced diabetic rats” Methodology: Randomized Control Trial, conducted at Department of Pharmacology, Riphah University, in collaboration with NIH, Islamabad, Pakistan, from September 2019 to August 2020. Healthy, 40, albino rats were randomly divided into Groups A and B. Group B was further subdivided into: GroupB1 (Diabetic Control), Group B2 (Aloe Vera whole Leaf treated), GROUP B3 (Sitagliptin treated), n=10 each, (after diabetes induction). At Day 60, FBS and serum triglycerides were measured in all rats. SPSS version 25 was applied for statistical analysis. One-way ANOVA test was used for assessing any difference in the mean values. Post-hoc Turkey analysis was done to compare inter-group mean differences. P value of <0.05 was considered significant. Results: On terminal sampling, mean FBS of Rats in Group A was 82.40 mg/dl, Group B1 498.40mg/dl, Group B2 89.30mg/dl and Group B3 93.00mg/dl; Serum Triglycerides for Group A 125.40mg/dl, B1 221.00mg/dl, B2 112.50mg/dl, B3 125.00mg/dl respectively. In Group B2 and Group B3 significant reduction in fasting blood glucose and triglycerides is observed, compared to Group B1, with no statistically significant intergroup differences in results of Group B2 and B3. Conclusion: Aloe Vera whole leaf extract significantly decreased fasting blood glucose and triglyceride levels with nearly similar efficacy to Sitagliptin in diabetic rats.